The Diagnostic Value of Electromyography in Identifying Patients With Pain-Related Temporomandibular Disorders - Szyszka-Sommerfeld, Liliana (Front Neurol, 2019)
Introduction: Orofacial pain disorders can be divided into several subgroups. One of them is temporomandibular disorders (TMD) with recognizable signs such as joint noises, limitations in the range of motion, or mandibular deviation during function and symptoms—pain in the muscles or joint. Surface electromyography (sEMG) is a diagnostic tool that ensures reliable and valid evaluation of muscle activity. sEMG detects electrical potentials and on this account may conceivably be employed in the TMD recognition. The aim of this study was to assess the sensitivity, specificity, and accuracy of electromyography in diagnosing subjects with temporomandibular disorders, including pain-free TMD and pain-related TMD. Methods: The sample comprised 88 patients with cleft lip and palate and mixed dentition. TMD has been recognized on the grounds of Axis I of the Research Diagnostic Criteria for TMD (RDC/TMD). To evaluate the electrical activity of the temporal and masseter muscles in the rest position and during maximum voluntary contraction, a DAB-Bluetooth Instrument (Zebris Medical GmbH, Germany) was used. The analysis of the receiver operating characteristic (ROC) curve gave information about accuracy, cut-off point value, sensitivity and specificity of the normalized sEMG data. Results: The highest diagnostic efficiency of sEMG in terms of identifying subjects with TMD and pain-related TMD was observed for the mean values of temporal and masseter muscle activity as well as the Asymmetry Index of the masseter muscles in a rest position. A moderate degree of EMG accuracy in differentiating between pain-related TMD and non-TMD children was observed for the mean values of masseter muscle activity and the Asymmetry Index of the masseter muscles at rest. Conclusion: An evaluation of electromyography exhibits its diagnostic usability in recognition of patients with pain-related TMD and it could be used as an adjunctive tool in the identification of this disorder. Clinical Trial Registration: This clinical research was registered in the ClinicalTrials.gov database under the number NCT03308266.